Strategi Komunikasi Terapeutik Antara Dokter Dengan Pasien Rawat Inap Lansia Di Klinik Nadhifa Al-ghiffari Bandung - Wismagian, Octavius Jonathan Noel; Destiwati, Rita; Rochimah, Haris Annisari Indah Nur (eProceedings of Management, 2024)
Building a relationship based on trust and openness through therapeutic communication efforts is importantso that the problems experienced by patients can be known and overcome by health workers. Elderly patients are differentwith patients in general, there are physiological and psychological factors in elderly patients that can hinder effective communication efforts.inhibit effective communication efforts. Ineffective communication can increaseuncertainty for the patient. This study aims to determine effective therapeutic communication strategiesbetween doctors and elderly inpatients at the Nadhifa Al-Ghiffari clinic in Bandung. This research utilizestheoretical views in Uncertainty Reduction Theory to examine communication strategies by doctors whenhandling uncertainties and barriers of therapeutic communication with elderly patients. This researchusing a qualitative approach. The informants in this study were five people, the data collection was carried outusing in-depth interviews, direct observation, and document search. The result of the researchThe results showed that the doctor had applied the stages and techniques of therapeutic communication well to the elderly inpatients at the Nadhifa Al-Ghaza Clinic.elderly inpatients at Nadhifa Al-Ghiffari Clinic Bandung. In addition, doctors have also carried out active and interactive strategies in communicating.active and interactive strategies in communication. Active strategies are carried out when communicating with third parties, namelypatient's family, while interactive strategies are carried out by doctors when communicating directly with elderly inpatients.elderly inpatients. Keywords-communication barriers, doctor communication, elderly patients, uncertainty reduction, therapeutic.